PELATIHAN DAN PENGEMBANGAN KARAKTER POSITIF SISWA MELALUI PENGENALAN SEJAK DINI ( STUDI KASUS SDN SENDANG LAOK, KEC LABANG, KAB. BANGKALAN, MADURA ) (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
Writing this paper aims to explain the importance of Student Positive Character Training and Development through Early Recognition, which is conducted for students at Sendang Laok Elementary School, Madura. As for the background of this writing because Education is a matter that must be taken by each individual for the continuity of their lives and future and benefit their families, nations and countries. As individual social beings, they certainly cannot live alone. Every individual needs to interact and cooperate with other individuals like social beings who always need other people to be able to live their lives. In this case the students need to recognize in depth and practical how the meaning of cooperation in the team will eventually be incorporated in an agency or organization later. For this reason, students need to recognize the potential or positive character they have in order to foster self- confidence and become a better generation for the nation, especially motivating themselves to continue learning as students in the 6th grade of elementary school..